Virus Diseases in Wild Plants - Richards, Marilyn Gertrude (My University, 1954)
This thesis consists of a part of a long-term statistical survey of virus diseases in wild plants being conducted by Dr. W. D. MacClement. The Royal Botanical Gardens, Hamilton, Ontario, is the field of investigation. The distribution, frequency, season variation and rate of spread of the virus diseases were studied. The research was conducted in six parts: (a) A survey of virus in wild plants; (b) A detailed study of virus in one genus in one area; (c) The study of virus in three species in each of three line transects; (d) Spread of virus in lawn weeds; (e) Comparison of natural virus infection in crop and wild plants. (f) Carry-over of virus in over-wintering plant structures.
Keywords: Botany; Plants; Virus; Viruses; viral; diseases; wild; infection